Borehole image-based evaluation of coral reef porosity distribution characteristics. Issue 7 (3rd October 2017) - Wang, Jin-chao; Wang, Chuan-ying; Zhu, Chang-qi; Hu, Sheng
ABSTRACT: In this study, we used digital borehole image camera to obtain images of porosity distribution in coral reefs in South China Sea, and developed an effective evaluation system for such distributions. First, the original images are preprocessed, allowing the pore regions to be automatically detected. The depth and sectional functions are established to measure five parameters: pore count, pore radius, radius concentration rate, total pore area ratio, and fractal dimension count. These are used to calculate the characteristic values of porosity distributions, and their fuzzy relationships are used to build the evaluation model, determine the Hamming distances between distributions, and establish the relationships between the characteristics and coral rock classifications. Test results from applying the method on a deep borehole image segment show the results to be consistent with other methods, and the following conclusions can be reached: (1) the porosity evaluation model is a viable way to analyze porosity distribution characteristics; (2) the resulting classification method is viable; and (3) porosity distribution analysis on coral reefs has important implications.